Efficacy of Preoperative Intramuscular Testosterone Therapy for Micro-phallic Hypospadias - Ali, Md Ayub; Palit, Paritosh Kumar; Hasanuzzaman, Md (Bangladesh Journal of Child Health, 2019)
Background: Surgical corrections of genital defects were formally proposed when the size of the penis is sufficient to permit easy surgical repair. In micro phallic hypospadias, temporary stimulation with testosterone either topical or parenteral to enlarge the penile size has been reported. The aim of this study was to evaluate the efficacy of preoperative intramuscular testosterone therapy in micro phallic hypospadiac patients. Methodology: This prospective interventional study was carried out in the division of pediatric surgery, Dhaka Shishu (Children) Hospital. A total of 70 boys having micro phallic hypospadias were included in the study from July 2014 to December 2017. All patients received 3 dose of IM testosterone (2mg/kg) at 1 month interval. Alteration of penile length, glans width and the adverse effects of testosterone therapy were recorded. Data were analyzed by using SPSS version 22. Results: The mean length of penis before treatment was 2.61±0.57 cm, and after intramuscular testosterone was 3.93±0.39 cm, which is statistically significant (p<0 .05).The mean glans width before treatment was 1.09±0.18 cm and after treatment was 1.62±0.11 cm (p < 0.05).Few adverse effect were noted. Conclusion: Significant penile growth was observed with less adverse effects after using intramuscular testosterone. Hormone therapy preceding surgical correction of micro phallic hypospadias improves aesthetic and functional qualities of the penis. Bangladesh J Child Health 2019; VOL 43 (2) :85-89